Strategi Pengajaran Guru PAI dan Dampaknya terhadap Motivasi Belajar Siswa dalam Mata Pelajaran Pendidikan Agama Islam di SMP Negeri 61 Surabaya - Bachtiar, Mochamad Nur; Mas'ud, M.; Amiruddin, Amiruddin (An-Nafah: Jurnal Pendidikan dan Keislaman, 2023)
The problem in this study is the lack of student motivation in Islamic education subjects. The formulation of the problem is how the role of PAI teachers in increasing motivation, what are the implications of the role of PAI teachers, and the supporting and inhibiting factors of the role of PAI teachers in increasing students' learning motivation in Islamic Religious Education subjects at SMP Negeri 61 Surabaya.This type of research is field research, namely research whose object is about the role of PAI teachers in increasing students' learning motivation in Islamic Religious Education subjects at SMP Negeri 61 Surabaya. This study uses data collection techniques, namely: observation, interviews and documentation. Broadly speaking, the role of PAI teachers in increasing students' learning motivation in Islamic Religious Education subjects at SMP Negeri 61 Surabaya, teachers as learning leaders, teachers as learning facilitators, teachers as motivators, teachers as learning inspirations, teachers as examples (suri role model), the teacher as a learning moderator, the teacher as an evaluator, the teacher as the manager of the teaching and learning process. The implications of the role of PAI teachers are expected to increase students' learning motivation according to their abilities and teaching methods so that they can attract students' attention. In addition, the inhibiting factors experienced by teachers are environmental factors and due to factors from outside the student's personal self. Supporting factors are internal factors, namely the motivational drive that exists within students and external factors that can support are teachers, parents and the community..